Triboelectric Nanogenerators Based on the Archimedes Wave Swing for Water Wave Energy Harvesting: Physics Experiments and Simulations. Issue 4 (2nd February 2023) - Yang, Shaohui; Tang, Ping; Huang, Yan; Du, Zhichang; Fan, Jianyu; Xiao, Guohong
Abstract : Triboelectric nanogenerators (TENGs) have demonstrated enormous potential as a novel technology for water wave energy harvesting and self‐powered sensors. However, most of the reported studies have focused on sea‐level energy capture. The energy below the sea level including potential energy and kinetic energy is also highly abundant. Herein, a prototype TENG based on the Archimedes wave swing (AWS‐TENG) is proposed. The AWS‐TENG is a unique wave energy conversion device since it is completely submerged and offers excellent concealment. The physical model of AWS‐TENG is developed by investigating structural properties and wave energy theory. Furthermore, a V‐Q‐X equation analysis of the TENG in vertical separation mode is carried out via finite element simulation to better understand its dynamic electrical characteristics. In addition, experimental tests are carried out on the system. The experimental results show that AWS‐TENG achieves a power density output of 7.9 mW m −2 at 4.5 Hz, which is sufficient for fast capacitor charging and application circuits. This proposed TENG design offers a unique way to capture wave energy. Abstract : A prototype triboelectric nanogenerator (TENG) based on the Archimedes wave swing (AWS‐TENG) is proposed. The AWS‐TENG is a unique wave energy conversion device since it is completely submerged and offers excellent concealment.